Assessing the Impact of COVID-19 on Unemployment in Province of Bali, Indonesia - Made Antara; Made Sri Sumarniasih (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
The research aims are (1) to analyze the impact of the COVID-19 pandemic on disturbances in the province of Bali, and (2) to analyze the impact of the COVID-19 pandemic on unemployment by regencies/cities in Bali Province. Due to the concerns of direct contact with an exposed individual, prolonged job duties without good rest, and disrupted wake and sleep phases, the phobia of being contaminated has increased the likelihood of tension and worrying among healthcare workforces. The COVID-19 pandemic not only hurts the performance of the national economy but also has an impact on the regional economy of Bali, which incidentally is a subsystem of the national economic system. Sources of data are secondary sources namely the Central Statistics Agency of Bali Province and the Population and Employment Service of the Province of Bali and Regencies throughout Bali. The data analysis methods were descriptive statistics, before and after/the COVID-19 pandemic, and qualitative descriptive methods. The results showed that (1) the COVID-19 pandemic had an impact on increasing unemployment in Bali Province by 106,150 nine districts/cities that were affected, and three regencies/cities in Bali’s tourism development centers, namely Badung, Gianyar, and Denpasar. The research is interesting in that it shows how the COVID-19 epidemic is contributing to Bali’s rising unemployment rate. According to the study’s findings, the government has offered a variety of social services and facilities to ensure that they are appropriate for the intended beneficiaries. However, the government still needs to offer agricultural skill training and other resources to workers who transition from tourism to agriculture. In the recovery phase, the government has indeed relaxed various health care requirements for tourists visiting Bali tourist destinations. However, other strategies need to be implemented, such as increasing the number of visa-free countries for tourist visits to Indonesia and Bali, considering that Bali tourism is the driver of Bali’s economy.